ASME 2008 Summer Bioengineering Conference, Parts a and B 2008
DOI: 10.1115/sbc2008-192418
|View full text |Cite
|
Sign up to set email alerts
|

Shape Effects of Filaments Versus Spherical Particles in Flow and Drug Delivery

Abstract: Interaction of spherical particles with cells and within animals has been studied extensively, but the effects of shape have received little attention. Here we use highly stable, polymer micelle assemblies known as filomicelles to compare the transport and trafficking of flexible filaments with spheres of similar chemistry. In rodents, filomicelles persisted in the circulation up to one week after intravenous injection. This is about ten times longer than their spherical counterparts and is more persistent tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Cylindrical micelles with a certain aspect ratio would circulate about ten times longer in vivo than spherical micelles. [133] At the same time, studies had also demonstrated that polypeptide fiber structures with larger aspect ratios had lower cytotoxicity. [134] Therefore, in recent years, researchers have begun to explore the application of BCP micelles with uniform sizes and morphologies in the biological field.…”
Section: Application Of Functionalized Precise Self-assembled Structuresmentioning
confidence: 99%
“…Cylindrical micelles with a certain aspect ratio would circulate about ten times longer in vivo than spherical micelles. [133] At the same time, studies had also demonstrated that polypeptide fiber structures with larger aspect ratios had lower cytotoxicity. [134] Therefore, in recent years, researchers have begun to explore the application of BCP micelles with uniform sizes and morphologies in the biological field.…”
Section: Application Of Functionalized Precise Self-assembled Structuresmentioning
confidence: 99%